(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Every individual knows that there are things in our environment that might cause positive and negative impacts that affect our duties as an office worker. This is how researchers ended up studying the Impacts of the work environment on the productivity of employees at the Public Employment Service Office in Quezon City. PESO is a government office that helps its community to get a job under any circumstances. The result of the study revealed the impact of the office environment on the productivity of employees in PESO in terms of the cited variables: 2.1 Workplace Ambiance- the employee’s motive to work effectively if they have a good workplace environment. 2.2 Physical Layout- the employees who have their own workplace space can be productive. 2.3 Office Equipment - Having good quality office supplies and equipment, employees can work efficiently and produce quality work. 2.4 Ergonomics- The ergonomically designed equipment used by the workers makes them feel comfortable, which contributes to their ability to perform their daily duties. 2.5 Workspace- the employees feel comfortable having a physical workplace setting to do their tasks smoothly. The results of the gathered data conclude that environment, such as Workplace Ambiance, Office Layout, Office Equipment, Ergonomics, and Workspace, has a great impact when it comes to the quality and level of productivity of employees as a part of the office environment. This might have a positive and negative impact on the productivity of employees. Having a positive work environment is essential for any organization to succeed. It encourages employees to be more productive, creative, and motivated in work.